2012
DOI: 10.4103/1735-3327.95227
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the cleaning capacity of Mtwo and ProTaper rotary systems and manual instruments in primary teeth

Abstract: Background:Root canal cleaning is an important step in endodontic therapy. In order to develop better techniques, a new generation of endodontic instruments has been designed. The aim of this study was to compare the effectiveness of manual K-files (Mani Co, Tokyo, Japan) and two rotary systems–Mtwo (Dentsply-Maillefer, Ballaigues, Switzerland) and ProTaper (VDW, Munich, Germany)–for root canal preparation in primary molars.Materials and Methods:India ink was injected to 160 mesiobuccal and distal root canals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 23 publications
(46 reference statements)
5
63
1
7
Order By: Relevance
“…Kummer et al, proved the manual instrumentation removed more dentine when compared with rotary instruments in primary teeth [20]. Azar et al, reported no significant differences in cleaning efficiency between Manual K-files and the Mtwo and ProTaper rotary systems in primary teeth [21].…”
Section: Discussionmentioning
confidence: 99%
“…Kummer et al, proved the manual instrumentation removed more dentine when compared with rotary instruments in primary teeth [20]. Azar et al, reported no significant differences in cleaning efficiency between Manual K-files and the Mtwo and ProTaper rotary systems in primary teeth [21].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, rotary instrumentation dramatically reduces the working time, which is a very interesting aspect to consider for pediatric patients (1,(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Access cavity preparation was done using endo access bur to obtain straight line access, unroofing of the chamber was done and the pulp extripation was done for both the groups [13]. In Group 1, the root canals were instrumented manually with K-files with the step-back technique up to file ISO size 30 [14], and in Group 2 initially a glide path was prepared to allow free insertion of a #20 K-file to its working length, which allowed free insertion of the SAF to the full length of prepared canal [13].…”
Section: Root Canal Preparationmentioning
confidence: 99%
“…In Group 1, the root canals were instrumented manually with K-files with the step-back technique up to file ISO size 30 [14], and in Group 2 initially a glide path was prepared to allow free insertion of a #20 K-file to its working length, which allowed free insertion of the SAF to the full length of prepared canal [13].…”
Section: Root Canal Preparationmentioning
confidence: 99%
See 1 more Smart Citation